2011
DOI: 10.1007/s12028-011-9606-8
|View full text |Cite
|
Sign up to set email alerts
|

Optic Nerve Ultrasound for the Detection of Raised Intracranial Pressure

Abstract: Bedside ONSD measurement, performed by neurointensivists, is an accurate, non-invasive method to identify ICP > 20 mmHg in a heterogeneous group of patients with acute brain injury. ONSD ≥0.48 cm has the greatest accuracy, however, internal validation of ONSD criteria may be required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
310
4
25

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(347 citation statements)
references
References 22 publications
(40 reference statements)
8
310
4
25
Order By: Relevance
“…4 Previous studies have shown high levels of correlation between optic nerve sheath width by ultrasonography and intracranial pressure measured directly through invasive monitors. [11][12][13] A study by Neudorfer et al 14 showed that increased optic nerve sheath width by orbital ultrasonography correlated well with the final diagnosis of papilledema or pseudopapilledema in a pediatric population. Our study aims to further evaluate the role of orbital ultrasonography in distinguishing papilledema from pseudopapilledema in a cohort of adult patients who were referred to the neuroophthalmology service for the evaluation of swollen optic nerves.…”
Section: Introductionmentioning
confidence: 99%
“…4 Previous studies have shown high levels of correlation between optic nerve sheath width by ultrasonography and intracranial pressure measured directly through invasive monitors. [11][12][13] A study by Neudorfer et al 14 showed that increased optic nerve sheath width by orbital ultrasonography correlated well with the final diagnosis of papilledema or pseudopapilledema in a pediatric population. Our study aims to further evaluate the role of orbital ultrasonography in distinguishing papilledema from pseudopapilledema in a cohort of adult patients who were referred to the neuroophthalmology service for the evaluation of swollen optic nerves.…”
Section: Introductionmentioning
confidence: 99%
“…11, 25 Rajajee et al 25 conducted a comparison between ONSD and I-ICP measurements, EVD, and intraparenchymal monitoring, indicating that the optimal ONSD for detection of ICP ≥ 20 mm Hg was ≥ 0.48 cm (sensitivity 96% and specificity 94%). Spearman's correlation coefficient of an ONSD of 0.52 cm for detection of ICP ≥ 20 mm Hg was 0.73.…”
Section: Discussionmentioning
confidence: 99%
“…Spearman's correlation coefficient of an ONSD of 0.52 cm for detection of ICP ≥ 20 mm Hg was 0.73. 25 The main limitation of this method is that the measurement accuracy corresponds to the operator's experience and equipment, as well as the fact that the ONSD criterion (i.e., cutoff for ICP hypertension) is not well established. 13,25 All of the aforementioned drawbacks can be counterproductive to the implementation of this method and its effectiveness in ICUs.…”
Section: Discussionmentioning
confidence: 99%
“…KİB yüksekliğini işaret eden eşik değer çeşitli yayınlarda 4,8-5,8 mm arasında gösterilmekle birlikte (43)(44)(45)(46) bir konsensusdan söz etmek mümkün değildir. Optimal değer olarak 5 mm'nin kabul edilmesi yerindedir.…”
Section: Orta-hat şIftinin Sonografik öLçümüunclassified